Awareness and use of the national archives: evidence from the Volta and Eastern regional archives, Ghana - OTU, Bernard Okoampah; ASANTE, Edward (Faculdade de Filosofia e Ciências, 2015)
The study examined the awareness and use of the Volta and Eastern regional archives of Ghana. Archives play a pivotal role in documenting the historical memory of humans. Archives as institution and records as documents are generally seen by academics and other users as a passive resource to be exploited for various historical and cultural purposes. The study employed the survey design with data obtained analysed using descriptive statistics. The population of the study included inhabitants of the defined geographical area who where 18years and above with some level of education from secondary to tertiary level. Findings revealed the lack of awareness of the Volta and Eastern regional archives by the inhabitants within that geographical area. Based on the findings, it was recommended that the archives should create more awareness through outreach programmes during festive occasions thus breaking the traditional pattern of waiting for users to come and patronise them to ‘marketing’ their services to the people to achieve better results